Itraconazole perturbs colorectal cancer dormancy through SUFU-mediated WNT inhibition - Semiramis A. Popova; Simon J. A. Buczacki (Molecular & Cellular Oncology, 2018)
Cancer cell dormancy is an important source of treatment failure. We studied the molecular characteristics and functional behaviour of dormant colorectal cancer cells finding them to be a differentiated yet plastic population. Organoid drug screening identified itraconazole perturbs dormancy through non-canonical hedgehog signalling effects on the WNT pathway.